Crystal structure of bis{2-[(E)-(4-methoxylbenzyl)- iminomethyl]phenolato-j2N,O1}nickel(II) - Bahron, Hadariah; Mohd Tajuddin, Amalina; Wan Ibrahim, Wan Nazihah; Fun, Hoong Kun; Chantrapromma, Suchada (International Union of Crystallography, 2014)
The asymmetric unit of the title compound, [Ni(C15H14NO2)2], comprises an NiII cation, lying on an inversion centre, and a Schiff base anion that acts as a bidentate ligand. The NiII cation is in a square-planar coordination environment binding to the imine N and phenolate O atoms of the two Schiff base ligands. The N- and O-donor atoms of the two ligands are mutually trans, with Ni—N and Ni—O bond lengths of 1.9191 (11) and 1.8407 (9) A ° , respectively. The plane of the methoxybenzene ring makes a dihedral angle of 84.92 (6) with that of the phenolate ring. In the crystal, molecules are linked into screw chains by weak C—H O hydrogen bonds. Additional C—H O hydrogen bonds, together with C—H contacts, arrange the molecules into sheets parallel to the ac plane.